Low SOCS3 expression in CD4+ T cells from pemphigus vulgaris patients enhanced Th1- and Th17-cell differentiation and exacerbated acantholysis via STAT activation. (October 2022) - Lin, Xiaoying; Chen, Mengxin; Li, Xiaolan; Wang, Hong; Bao, Yanyi
Abstract: Objective: Pemphigus vulgaris (PV) is a chronic inflammatory autoimmune blistering disease. Aberrant SOCS3/STAT pathway activation is associated with many autoimmune diseases. This study explored the relationship between activation of the SOCS3/STAT pathway and abnormally increased proportions of Th1 and Th17 cells in the peripheral blood of PV patients as well as the effect of CD4 + T cells with abnormal SOCS3/STAT pathway activation on acantholysis. Methods: In PV patients, the proportions of Th1 and Th17 cells in peripheral blood, the levels of IFN-γ and IL-17 in serum and the mRNA levels of SOCS3 and STAT1/3 in CD4 + T cells were detected. Then, SOCS3-knockdown primary CD4 + T cells were prepared, and cocultured with HaCaT cells. Finally, after SOCS3 knockdown and coculture, CD4 + T cells were collected, and the proportions of Th1 and Th17 cells, the protein levels of STAT1/3 and p-STAT1/3, and the levels of IFN-γ and IL-17 were measured. After 2 days of coculture, HaCaT cells were collected, inflammatory factors mRNA expression and acantholysis were assessed. Results: In PV patients, the proportions of Th1 ( P = 0.016) and Th17 ( P = 0.045) cells and the levels of IFN-γ ( P = 0.010) were significantly increased. SOCS3 mRNA in CD4 + T cells was significantly decreased ( P = 0.008), whereas STAT1 ( P = 0.043) and STAT3 ( P = 0.004) mRNA were significantly increased. After SOCS3 knockdown, the proportions of Th1 ( P < 0.001) and Th17 ( P = 0.006) cells, the levels of IFN-γ ( P < 0.001) and IL-17 ( P = 0.001), and the protein levels of p-STAT1 ( P = 0.001) and p-STAT3 ( P = 0.003) were significantly increased in the CD4 + T-shSOCS3–1 group. In the coculture system, the proportions of Th1 ( P < 0.001) and Th17 ( P < 0.001) cells, the levels of IFN-γ ( P < 0.001) and IL-17 ( P < 0.001), and the number of cell fragments ( P < 0.001) were significantly increased in the CD4 + T-shSOCS3–1+HaCaT-PV-IgG group, whereas the protein level of desmoglein3 (Dsg3) was significantly decreased. In addition, PV-IgG significantly increased IFN-γ and IL-6 mRNA in HaCaT cells. Conclusion: Low SOCS3 expression in CD4 + T cells from PV patients leads to overactivation of STAT, which causes CD4 + T cells to overdifferentiate into Th1 and Th17 cells. Additionally, PV-IgG-induced local inflammation in skin lesions, which is mediated by IFN-γ and IL-6, can aggravate this phenomenon. Furthermore, low SOCS3 expression in CD4 + T cells further exacerbates PV-IgG-induced acantholysis. Therefore, upregulating the expression of SOCS3 in CD4 + T cells of PV patients and maintaining the balance of the IFN-γ/STAT1/SOCS3 and IL-6/STAT3/SOCS3 pathways can alleviate acantholysis in patients with PV. Highlight: For the first time, the low expression of SOCS3 and abnormally activited STAT signaling in CD4 + T cells of patients with pemphigus vulgaris (PV) were identified. The synergistic immune response of Th1/Th17 cells seems to play an important role in the pathogenesis of PV. Low SOCS3 expression in CD4 + T cells could aggravate acantholysis.